Bible and ethics in the Christian life: a new conversation - Birch, Bruce Charles (Augsburg Fortress, 2018)
Part I.The Bible as moral witness --1.A two-part consensus --2.Foundations of the biblical text in community witness --3.Biblical authority --4.Interpreting the biblical witness --part II.Elements of the moral life --5.What are morality, ethics, and Christian ethics? --6.Moral formation --7.Moral discernment and action -- part III.The Bible, ethics, and the moral life --8.Witness and practice --9.The church and the moral life --10.Summary and challenge.